2019
DOI: 10.24839/2325-7342.jn24.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Training Methods, Opinions of Political Correctness, and Perceptions of Microaggressions

Abstract: Through her leadership and commitment to diversity, she has made the Journal and Psi Chi an even better organization. Following her lead, Psi Chi Journal has implemented a diversity statement and is committed to supporting this statement and standards. Dr. Domenech Rodríguez has left a long lasting impact on Psi Chi-one that we can all be proud of. ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929. Its mission: "recognizing and promoting excellence in the science and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Whilst WD and CPC are inversely correlated ( r = −.23, p < .001), a principal component analysis showed that they are discrete. Subsequent to our fieldwork, a more recent study (Smith & Percy, 2019) has used an adapted version of the CPC, which included six items each for high PC and low PC. Nevertheless, the Smith and Percy (2019) measure still refers explicitly to PC raising the potential for a social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst WD and CPC are inversely correlated ( r = −.23, p < .001), a principal component analysis showed that they are discrete. Subsequent to our fieldwork, a more recent study (Smith & Percy, 2019) has used an adapted version of the CPC, which included six items each for high PC and low PC. Nevertheless, the Smith and Percy (2019) measure still refers explicitly to PC raising the potential for a social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to our fieldwork, a more recent study (Smith & Percy, 2019) has used an adapted version of the CPC, which included six items each for high PC and low PC. Nevertheless, the Smith and Percy (2019) measure still refers explicitly to PC raising the potential for a social desirability bias. There remains a need to develop a measure of PC that is both robust and pragmatic.…”
Section: Discussionmentioning
confidence: 99%
“…The research on cognitive diversity in this issue overwhelmingly measure White students in these studies due to local population which is limiting. These studies encourage the uplifting of voice (d3) by recommending the improvement of the introductory texts used in classes (Cramblet Alvarez et al, 2019), ways to better communicate the problems caused by microaggressions (Patterson & DomenechRodríguez, 2019;Smith & Percy, 2019), or strategies to improve professional identities of students of color (Cabrera et al, 2019).…”
Section: Applying a Djs Lens To This Special Issuementioning
confidence: 99%
“…In the present case, I will apply the DJS lens questions collectively to the research presented in this special issue. These manuscripts collectively represent research aimed at identifying conditions that people recognize as diverse contributions to the field (Cramblet Alvarez et al, 2019), measuring the impact of diversity training on microaggressions (Smith & Percy, 2019), examining the general perception of microaggressions (Patterson & DomenechRodríguez, 2019), explaining responses to antigay bullying (Katz & Klainberg, 2019), and advancing the diverse development of a research ers' identity (Cabrera, Hatch, & Lovell, 2019). This process should reveal the degree to which the corpus of papers in this issue adequately addresses the breadth and depth of DJS.…”
Section: Applying a Djs Lens To This Special Issuementioning
confidence: 99%
See 1 more Smart Citation